A genotoxicity assessment approach for botanical materials demonstrated with Poria cocos. (October 2021) - Sun, Bin; Huang, Bowen; Sica, Vincent P.; Baker, Timothy R.; Pfuhler, Stefan
Abstract: Safety assessment of botanical materials often reveals genotoxicity data gaps. However, there are no harmonized regulatory genotoxicity testing approaches for botanical materials. Furthermore, literature genotoxicity testing reports often lack clear definition of the botanical materials (genus species, plant part, etc.) and/or analytical characterization. Here, upon a review of available regulatory testing batteries for botanicals, the authors conclude that an in vitro 2-test battery, consisting of the Ames test and the in vitro human lymphocyte micronucleus assay (HLM), is appropriate to assess the genotoxicity of botanical materials. This approach was then illustrated using a Poria cocos (PCS) botanical material as a case study. Before the genotoxicity testing, an analytical characterization coupled with in silico approach assured appropriate characterization of PCS and helped inform the genotoxic potential of the triterpenes that drive the genotoxicity assessment. The literature search and DEREK screening did not reveal a genotoxicity concern or a genotoxicity structural alert. PCS was then tested in OECD guideline compliant Ames and in vitro HLM and the negative results from this 2-test battery confirmed the absence of a genotoxic potential of the PCS. This fit-for-purpose approach is expected to be useful to fill genotoxicity data gaps for botanical materials. Highlights: An Ames and in vitro MNT batteryis suggested to address the genotoxicity of botanical materials. The genotoxicity assessment approach for botanicals also includes an analytical characterization and in silico assessment. A case study with Poria cocos (PCS) mushroom powder was used to illustrate this approach in a real-life assessment. The case study results demonstrated the absence of genotoxic potential for PCS.